The DEVELOPMENT OF HYPERMEDIA LEARNING MEDIA IN AN EFFORT TO IMPROVE HIGH ER ORDER THINKING SKILLSS STUDENTS IN HIGH SCHOOL ECONOMICS CLASS X SUBJECTS: learning media, hypermedia, higher order thinking skills - Robi Maulana; Syafaatul Hidayati (UIR PRESS, 2022)
This study aims to develop Hypermedia Learning Media in an Effort to Improve students' higher order thinking skills in class X high school economics subjects. In this research, it uses the step of model development studies. The stage stage of the development studies research model according to akker such as preliminary research, prototyping stage, summative evaluation, systematic reflection and documentation. The hypermedia learning media developed was declared feasible This feasibility was assessed by two experts consisting of media experts and material experts. Media experts stated that hypermedia learning media is excellent and feasible to use (91.1%). Material experts stated that hypermedia learning media is good and feasible to use (92.2%). The hypermedia learning media developed is very effective in improving higher-order thinking skills. The student posttest results also stated that hypermedia learning media is very effective (75%) in improving students' high-level thinking skills. The N-gain score obtained by students in this study was 0.5 (medium category). Hypermedia learning media is stated based on the results of teacher interviews to improve higher-order thinking skills. Meanwhile, students stated that hypermedia learning media is practically used (82%). Learning media requires an android 6.0 version smartphone which not all students have this version, and if using the ios version or website, it requires a stable connection to run hypermedia learning media online.